Trends in the Development of Vocational Education and Training Research Studies in Southeast Asia - Usup; Supriyono; Hardika; Dayati, Umi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This study examines the development trends of vocational training research studies in Southeast Asia in the period 2014 to 2024 using bibliometric analysis methods. By setting the keyword